At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve 2x^2+8x-7=-2 by completing the square

Sagot :

How to complete the square:

Step 1: Get all constants on one side.

[tex]2x^2+8x-7=-2\\2x^2+8x=5[/tex]

Step 2: If x² has a coefficient, divide it out.

[tex]2x^2+8x=5 \\ x^2+4x=\frac2{1}2[/tex]

Step 3: Halve the coefficient of x, square it, and add it to both sides.
(In this case, half of 4 is 2, and 2² is 4, so we add 4 to both sides.

[tex]x^2+4x=\frac{5}2\\x^2+4x+2=6\frac{1}2[/tex]

Step 4: Factor the left side. (And if the right side is a mixed number, change it to an improper fraction to make step 5 easier)
We set it up so that it will be a perfect square trinomial, so it'll always be equal to (x+half the coefficient of x)².

[tex]x^2+4x+2=6\frac{1}2\\(x+2)^2=\frac{13}2[/tex]

Step 5: Take the square root of each side.

(x+2)^2=\frac{13}2\\\sqrt{(x+2)^2}=\sqrt{\frac{13}2}

Step 6: Simplify and solve for x.

[tex]\sqrt{(x+2)^2}=\sqrt{\frac{13}2} \\ x+2=\frac{\sqrt{13}}{\sqrt{2}} = \frac{\sqrt{26}}2 \\\\ \boxed{x = -2\±\frac{\sqrt{26}}2}[/tex]

(Decimal answers if needed: approx -4.5495 and 0.54951)

2x² + 8x - 7 = -2
             + 2   + 2
2x² + 8x - 5 = 0
x = -(8) +/- √((8)² - 4(2)(-5))
                    2(2)
x = -8 +/- √(64 + 40)
                  4
x = -8 +/- √(104)
               4
x = -8 +/- 2√(26)
               4
x = -2 + 0.5√(26)
x = -2 + 0.5√(26)  x = -2 - 0.5√(26)